Cigarette graphic health warning labels and information avoidance among individuals from low socioeconomic position in the U.S. - McCloud, Rachel; Okechukwu, Cassandra; Sorensen, Glorian; Viswanath, K.; McCloud, Rachel Faulkenberry (Cancer Causes & Control, 2017)
Purpose: Although graphic health warning labels (GHWs) on cigarette packs have influenced cessation behaviors in other countries, no U.S. studies have explored the impact of avoidance of GHW content among individuals from low socioeconomic position (SEP). The purpose of this study was to determine the predictors of intention to avoid GHWs, and how avoidance impacts cessation intention, in a low SEP sample in the U.S.Methods: Data come from low SEP smokers (n = 541) involved in a field experiment. The participants responded to questions pre- and post viewing of GHWs assessing SEP, intention to avoid them, emotional reactions, and intention to seek health information or quit smoking. Backwards stepwise logistic regression determined the predictors for intention to avoid GHWs. Simple and adjusted logistic regression analyzed the association between avoidance and its main predictors and outcomes of intentions to seek information or quit smoking.Results: Predictors for avoidance included being somewhat addicted to cigarettes (OR 2.3, p = 0.002), younger than 25 (OR 2.6, p = 0.008), and having medium (OR 3.4, p < 0.001) or high (OR 4.7, p < 0.001) levels of negative emotional reaction to the labels. Intention to avoid GHWs was positively associated with the intent to look for health information about smoking (OR 2.2, p = 0.002). Higher levels of negative emotional reaction were positively associated with cessation behaviors, with high negative emotional reaction associated with nine times the odds of quitting (p < 0.001).Conclusions: Results indicate avoidance of GHWs does not detract from the labels' benefit and that GHWs are an effective means of communicating smoking risk information among low SEP groups.